QUALITY CONTROL OF 240 ML CUP PRODUCT PACKAGING USING SIX SIGMA AND FMEA METHODS TO REDUCE PRODUCT REJECT FAILURE AT PT. XYZ - riyanto (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
Manufacturers of bottled drinking water (AMDK) experience quality problems, namely the presence of defective products in each production that have not reached zero defects, especially in the 240 ml glass packaging production line which has the most product defects. Six Sigma can be defined as a methodology that provides tools for business process improvement with the aim of reducing process variation and improving product quality using the DMAIC approach (define, measure, analyze, improve and control). From the results of data measurement, it is obtained that for critical to quality (CTQ) locks based on the Pareto diagram, that 80% of the highest defects are in the type of lid defect where the lid defect itself consists of a lid leak, a lid rupture and an oblique lid. For the sigma level of bottled drinking water production at PT. XYZ before the application of the DMAIC method is 4.98 Sigma. And after the application of the DMAIC method is 5.00 Sigma. Then proceed with analyzing the causes of lid defects using causal diagrams and failure mode and effect analysis (FMEA). From the analysis of the cause and effect diagram, the factors that cause disability come from machine, material and human factors. Meanwhile, the RPN value before the application of the FMEA method was 221 RPN. And after the application of the FMEA method, the RPN value is 209 RPN. To improve the problem, it is necessary to check the condition of the sealing unit before carrying out the production process and sand the sealing unit once a week on an already uneven surface.